PEMANFAATAN PATI BIJI CEMPEDAK (Artocarpus champeden) UNTUK PEMBUATAN EDIBLE FILM - Syahrum Syahrum; Netti Herawati; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Cempedak seed was found to have high starchsof content and yet it has not been optimally utilized. Therefore this research was aimed to utilized the starchsof cempedak seed as material of edible film and to get the best formulations of added of starchscempedak seed. This research was conducted experimentaly by used Complete Randomized Design (CRD) with four treatmens and four replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatmens in this research include P1 (2 g starch cempedak seed), P2 (3 g starch cempedak seed), P3(4 g starch cempedak seed), and P4 (5 g starch cempedak seed). The results of research showed that addedof concentrations starchscempedak seed gave significantly affect on water content, thickness, solubility, water uptake, and water vapor transfer rateedible film. The best formulationswas obtained on the edible film with added of starch cempedak seed 5% which has water content of 21.98%, thickness of 0.15mm, solubility of 30.03%, water uptake of 62.74%, and water vapor transfer rate of 0.18g/m2/hour.Keywords:edible film, starch cempedak seed